Incorporation of biological factors in radiation therapy treatment planning - Brooke, M (2020)
Radiation therapy plays a crucial role in the treatment of cancer. Major developments in the field, including 3D tomographic imaging, intensity modulation and novel particle modalities, have all contributed to iterative improvements in precise dose delivery. These advances have enabled highly conformal tumouricidal dose deposition with improved healthy tissue sparing. Proton therapy, in particular, has become an increasingly adopted modality due to its favourable depth-dose profile, allowing for much of the dose to be localised within the target region, with virtually no dose leakage to tissues beyond the target. However, physical dose does not tell the full story; radiobiological mechanisms and their intermodality differences must be well-understood, as these explain the processes by which the energy deposited in cells leads to cell death and, ultimately, to clinical outcomes.